Bacillus Calmette-GuÉrin-Associated Cervical Spondylitis in a 3-Year-Old Immunocompetent Girl. Issue 12 (December 2020) - Imakiire, Ryo; Nishikawa, Takuro; Tominaga, Hiroyuki; Tawaratsumida, Hiroki; Imuta, Naoko; Koriyama, Toyoyasu; Nishi, Junichiro; Taniguchi, Noboru; Kawano, Yoshifumi
Abstract : Bacillus Calmette-Guérin (BCG)–associated osteomyelitis is a rare adverse event following BCG vaccination, and there have been no previous reports of BCG-associated cervical spondylitis. Here, we describe the case of a 3-year-old immunocompetent girl who developed BCG-associated cervical spondylitis and was successfully treated by prompt surgical drainage of the abscess and administration of isoniazid and rifampicin for 9 months without sequelae.